Chemical Principles of Boophone, Nerine, Crossyne, Clivia, Cryptostephanus, Haemanthus and Scadoxus of the South African Amaryllidaceae and Their Biological Properties - Nair, Jerald J.; van Staden, Johannes (Planta Medica, 2022)
The Amaryllidaceae features prominently amongst bulbous flowering plant families. Accommodating about a third of its species, South Africa affords a sound basis for Amaryllidaceae plant research. Boophone, Nerine, Crossyne, Clivia, Cryptostephanus, Haemanthus and Scadoxus have been well-represented in such endeavors. The account herein summarizes the studies undertaken between 2013 – 2020 on these genera in regards to their chemical and biological characteristics. A total of 136 compounds comprising 63 alkaloids and 73 non-alkaloid entities were described during this period from eighteen members of the title genera. The alkaloids were reflective of the structural diversity found in eight isoquinoline alkaloid groups of the Amaryllidaceae. Of these, the crinane (29 compounds), lycorane and homolycorine (11 compounds each) groups were the most-represented. The non-alkaloid substances were embracive of the same number of unrelated groups including, acids, phenolics, flavonoids and triterpenoids. A wide variety of assays were engaged to ascertain the biological activities of the isolated compounds, notably in regards to cancer and motorneuron-related diseases. There were also attempts made to determine the antimicrobial, anti-inflammatory and antioxidant effects of some of the substances. New information has also emerged on the herbicidal, insecticidal and plant growth regulatory effects of selected alkaloid principles. Coupled to the biological screening measures were in instances probes made to establish the molecular basis to some of the activities, particularly in relation to cancer and Parkinsonʼs disease.
Keywords: Alkaloid; Amaryllidaceae; Ethnobotany; Isoquinoline; South Africa